Influence of sugars on the foliar uptake of bentazone and glyphosate - Liu, Z.Q. (New Zealand Plant Protection, 2002)
The effect of sugars on the uptake of bentazone and glyphosate into bean (Vicia faba) and wheat (Triticum aestivum) foliage was studied The addition of 05 glucose or sucrose significantly increased the uptake of bentazone into bean and wheat leaves This effect was also observed in the presence of a surfactant especially in wheat Glucose and sucrose also improved the uptake of glyphosate into wheat leaves especially in combination with surfactants of low ethylene oxide content When used at 2 concentration both sugars completely overcame the antagonistic effect of an organosilicone surfactant (Silwet L77) on glyphosate uptake into wheat leaves The results are discussed in relation to the solute dose on the leaf surface as influenced by surfactants and sugars